2011
DOI: 10.1111/j.1365-2044.2011.06687.x
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil as single agent to facilitate awake fibreoptic intubation in the absence of premedication*

Abstract: SummaryRemifentanil is increasingly being used as the primary agent to provide sedation during awake fibreoptic nasal intubation. In this observational study, we aimed to determine the optimal effect site concentration of remifentanil, using a target controlled infusion based on the Minto pharmacological model, to provide optimal safe intubation conditions without the use of other sedatives ⁄ premedication and ⁄ or spray-as-you-go local anaesthesia. Twenty patients with anticipated difficult airway participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…36 In their study, the dose ranged from 0.2-0.5 lgÁkg -1 Ámin -1 , and the mean time from starting remifentanil to intubation was 12.5 min, suggesting that the effect-site concentration range would likely have exceeded those of Zhang et al 12 and (at the highest rates) those of Vennila et al 35 In three of the 24 patients, the respiratory rate fell to \8 breathsÁmin -1 and the lowest rate recorded was 2 breathsÁmin -1 . The patient population in their study was older (mean age 58) and mainly American Society of Anesthesiologists categories II and III.…”
Section: Remifentanilmentioning
confidence: 86%
See 2 more Smart Citations
“…36 In their study, the dose ranged from 0.2-0.5 lgÁkg -1 Ámin -1 , and the mean time from starting remifentanil to intubation was 12.5 min, suggesting that the effect-site concentration range would likely have exceeded those of Zhang et al 12 and (at the highest rates) those of Vennila et al 35 In three of the 24 patients, the respiratory rate fell to \8 breathsÁmin -1 and the lowest rate recorded was 2 breathsÁmin -1 . The patient population in their study was older (mean age 58) and mainly American Society of Anesthesiologists categories II and III.…”
Section: Remifentanilmentioning
confidence: 86%
“…Despite the very high concentrations of remifentanil used in their study, it is interesting to point out that mild coughing during tracheal intubation was still found in 15 of the 20 patients, and 13 patients reported mild to moderate discomfort. 35 There were no reported incidences of adverse events, specifically, desaturation to \90%, although the authors did not report the respiratory rates during the procedure. In stark comparison, Zhang et al found that a mean effect-site concentration of remifentanil of only 3.74 (±0.31) ngÁmL -1 was all that was necessary for AFOI without laryngeal topicalization.…”
Section: Remifentanilmentioning
confidence: 97%
See 1 more Smart Citation
“…Remifentanil is a synthetic opioid agonist with a short context sensitive half time of 3 min, rendering it easily titratable, thus minimizing respiratory depression [37]. It is an analgesic and antitussive [38], provides superior patient cooperation and tolerance to FOI, and provides better intubating conditions than propofol [31,38].…”
Section: Sedationmentioning
confidence: 99%
“…Aus Gründen der Sicherheit bietet sich zu diesem Zweck insbesondere das kurz wirksame und gut titrierbare 7 Remifentanil an, das an einigen Institutionen auch als alleiniges Analgosedativum selbst zur nasotrachealen fiberoptischen Wachintubation eingesetzt wird [31]. Zusätzlich werden bei Bedarf 1-2 mg/kgKG Lidocain (Boli à 1 ml der 2%igen Lösung) über den Arbeitskanal des Bronchoskops ("spray as you go") instilliert; diese werden durch den gleichzeitig insufflierten Sauerstoffstrom (s. unten) verteilt.…”
Section: Analgosedierungunclassified